Results of analyzing business processes throughout the ERP introduction in Serbia - Milošević Dragan (Trendovi u Poslovanju)
Business Process Management concept in Serbia is often applied for the first time during quality system implementation, or any of EBP solutions. EBP implementation process is very often seen as a panacea to the problems of poor business. In order to implement the ERP solution, it is necessary to perform fit-gap analysis. The process analysis, as a part of the fit-gap analysis opens many issues which were not so visible until then. This paper analyzes the shortcomings in business, considered through the analysis process and fit-gap analysis.